Synthesis of UV-Curable Biodegradable Polymer Membrane for Coating of Urea Fertilizer - Kaymaz, Aylin; Eren, Tarik (AMER CHEMICAL SOC, 2025)
Nitrogen is particularly important for promoting vegetative growth, which is essential for high yields in many crops. Urea contains a high concentration of nitrogen, making it an efficient source of this essential nutrient for plant growth. However, urea is highly soluble in water, which can lead to nitrogen loss through leaching or volatilization. Coating urea granules helps reduce these losses by controlling the release of nitrogen into the soil, improving nitrogen use efficiency and thus enhancing the uptake of nitrogen by plants. In the present study, urea granules were coated with polylactic acid and ultraviolet (UV)-curable methacryl-functional chitosan. After UV curing of the biopolymer-coated urea, the surface morphology was analyzed by scanning electron microscopy and Fourier transform infrared spectroscopy. The rates of urea release in distilled water were measured by UV spectroscopy. UV curing has been demonstrated as an effective method for coating granules, resulting in reduced rates of urea dissolution in water.
Keywords: urea fertilizer; controlled release; coating; UV curing; chitosan; PLA; CONTROLLED-RELEASE; Agriculture; Chemistry